Effect of tsunami load induced by earthquake at Manila Trench on transmission tower - Govindasamy N.; Syamsir A.; Mardi N.H.; Malek M.A. (Ain Shams University, 2023)
Earthquakes; Electric power transmission; Equations of motion; Nonlinear equations; Power plants; Transmissions; Coastal communities; High probability; Linear static analysis; Non-linear shallow water equations; Shallow water equations; Subduction zones; Transmission tower; Tsunami simulation; Tsunamis